Skončení pracovního poměru - Hermanová, Jaroslava; Galvas, Milan, 1949-2022; Masarykova univerzita. Katedra pracovního práva a sociálního zabezpečení (2011)
Rigorózní práce systematizuje poznatky z oblasti skončení pracovního poměru a je rozdělena do šesti kapitol. V úvodní kapitole se věnuji vzniku pracovního poměru, pracovní smlouvě, volbě, jmenování a obecnému vylíčení skončení pracovního poměru. . Dále je práce věnována právním úkonům účastníků pracovního poměru směřující k jeho skončení, kam jsem zahrnula jednotlivé způsoby skončení pracovního poměru, mimo jiné i hromadné propouštění a projednání s odborovou organizací.
Annotation: This rigorous thesis systematizes the knowledge how to terminate employment and it is divided into six chapters. In the preliminary chapter I tried to focus on the formation of employment relationship, employment contracts, election and appointment to the office and general representation of the employment relationship termination. I also refer to a possibility to withdraw from the employment contracts which leads to the dissolution of the employment relationship from the outset itself. Moreover the thesis deals with legal acts of the participants in the employment relationship which lead to the termination where I treat about the individual ways of termination of the employment relationship, mass release and dealing with the labour union. I did not forget to mention the legal events which lead to employment termination. I treat of the employment termination on the basis of the authoritative decision. Besides this the thesis contains termination of the employment relatio
Vedoucí práce: Milan Galvas
Rigorózní práce (JUDr.)--Masarykova univerzita, Právnická fakulta, 2011
Anglické resumé
Keywords: pracovní smlouvy; skončení pracovního poměru; labor contracts; termination of employment; rigorózní práce; doctoral dissertations